John Barth’s “Menelaiad” and Quantum Mechanics: The Sacrifice of Common Sense - Ali Emamipour; Farideh Pourgiv (Critical Literary Studies)
In the annals of the Greek myth, there has been a lacuna surrounding Menelaus and Helen’s relationship following the sack of Troy. What distinguishes Barth’s retelling of the Greek myth is filling this void through constructing a posthistory to the relationship the couple bear to each other and his giving voice to the concerns of Menelaus, a character who has always been in the recess of the canon. While a large body of research has approached Barth’s “Menelaiad” in light of literature of the absurd, this study, through adopting the stance of quantum mechanics on the nature of reality, will demonstrate that Barth’s work is anything but absurd. Establishing the framework of the article based on the uncertainty principle of quantum mechanics, the present study argues how the adoption of the subatomic reality, implied in Proteus’ advice, allows Menelaus to jettison his festering obsession with the causality behind Helen’s choice and re-embrace her.